Implementasi Akuntabilitas Pengelolaan Keuangan Desa (Kajian Penerapan Permendagri 20 Tahun 2018) - Syachbrani, Warka (Jurnal Ilmiah Akuntansi Peradaban, 2024)
This research aims to analyze the accountability of village financial management based on Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Fund Management. The intended accountability of village financial management consists of five stages, namely planning, implementation, administration, reporting and accountability for village finances. The data source in this research uses primary data. Data collection techniques were carried out using documentation and interviews. Data analysis was carried out using comparative descriptive. The results of this research indicate that Accountability for Financial Management in Munte Village, Tana Lili District, North Luwu Regency, South Sulawesi does not comply with the assessment indicators in Minister of Home Affairs Regulation No. 20 of 2018 at the planning, implementation and reporting stages, while at the administration stage and accountability stage it is appropriate.